PENGARUH JARAK DAN WAKTU TEMPUH TERHADAP PEMANFAATAN PELAYANAN DETEKSI DINI KANKER SERVIKS METODE INSPEKSI VISUAL ASAM ASETAT (IVA) DI PUSKESMAS TIGA JUHAR KABUPATEN DELI SERDANG - PEBRINA WANTI BR SARAGIH (LP2MTBM MAKARIOZ, 2018)
The problem of HIV/AIDS develops rapidly and becomes a threat globally. In order torestrain the spread of HIV/AIDS, the government provides health service facility with VCT (VoluntaryCounseling and Testing) Clinic. Patients who did not revisit VCT Clinic of RSUP Haji Adam Malik,Medan, increased to 46.2% in 2011 and 62.4% in 2012.The objective of the research was to find out the influence of the factors of consumers andhealth service providers on the use of revisit to the special service center (Pusyansus) of VCT clinicat RSUP Haji Adam Malik, Medan. The research was an explanatory survey; it was conducted fromJuly to September, 2013. The population was all 849 patients who had visited VCT clinic, and 90 ofthem were used as the samples. The data were gathered by conducting interviews withquestionnaires and analyzed by using multiple logistic regression analysis at α = 0.05.The result of the research showed that, statistically, the factors of consumers (perception onillness, perception on VCT service, and belief in the result of clinical diagnosis) and health serviceproviders (attitude of medical personnel, availability of medicines, and medical facility) had positiveand significant influence on the use of revisit to VCT clinic of RSUP Haji Adam Malik, Medan. Theperception on illness was the variable which had the most dominant influence on the revisit.It is recommended that the management of RSUP Haji Adam Malik, Medan: a) providecoordination with other agencies concerned such as the Health Service, KPA Province, KPAD,LSM, religious figures, and public figures to increase promotion about VCT through mass media,electronic, brochures/leaflets, and banners in order to prevent from the transmission of HIV/AIDS, b)develop doctors and counselors in communication technique with patients so that the effectivenessbetween doctors and patients in VCT clinic can be achieved, and counseling service to guaranteepatients' confidentiality and comfort, and c) motivate health care providers to participate in trainingregularly in order to improve their skill and insight so that patients do not wait too long to do VCT